Benefits and Harms of Standard Versus Reduced‐Dose Direct Oral Anticoagulant Therapy for Older Adults With Multiple Morbidities and Atrial Fibrillation - Kaleen N. Hayes; Tingting Zhang; Dae Hyun Kim; Lori A. Daiello; Yoojin Lee; Douglas P. Kiel; Sarah D. Berry; Andrew R. Zullo (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Dose reduction of direct oral anticoagulant (DOAC) medications is inconsistently applied to older adults with multiple morbidities, potentially due to perceived harms and unknown benefits of standard dosing. Methods and Results Using 2013 to 2017 US Medicare claims linked to Minimum Data Set records, we conducted a retrospective cohort study. We identified DOAC initiators (apixaban, dabigatran, rivaroxaban) aged ≥65 years with nonvalvular atrial fibrillation residing in a nursing home. We estimated inverse‐probability of treatment weights for DOAC dose using propensity scores. We examined safety (hospitalization for major bleeding) and effectiveness outcomes (all‐cause mortality, thrombosis [myocardial infarction, stroke, systemic embolism, venous thromboembolism]). We estimated hazard ratios (HRs) and 95% CIs using cause‐specific hazard‐regression models. Of 21 878 DOAC initiators, 48% received reduced dosing. The mean age of residents was 82.0 years, 66% were female, and 31% had moderate/severe cognitive impairment. After estimating inverse‐probability of treatment weights, standard dosing was associated with a higher rate of bleeding (HR, 1.18 [95% CI, 1.03–1.37]; 9.4 versus 8.0 events per 100 person‐years). Standard‐dose therapy was associated with the highest rates of bleeding among those aged >80 years (9.1 versus 6.7 events per 100 person‐years) and with a body mass index <30 kg/m2 (9.4 versus 7.4 events per 100 person‐years). There was no association of dosing with mortality (HR, 0.99 [95% CI, 0.96–1.06]) or thrombotic events (HR, 1.16 [95% CI, 0.96–1.41]). Conclusions In this nationwide study of nursing home residents with nonvalvular atrial fibrillation, we found a higher rate of bleeding and little difference in effectiveness of standard versus reduced‐dose DOAC treatment. Our results support the use of reduced‐dose DOACs for many older adults with multiple morbidities.